Peran Persepsi tentang Lingkungan Kerja Psikososial terhadap Komitmen Organisasional pada Lembaga Pendidikan Islam - Ugung Dwi Ario Wibowo (Universitas Islam Indonesia, 2015)
This objective of this research is to analyzed the role of perception toward psychosocial work environment on organizational commitment, a quantitative study to teacher and employeeof Islamic education institution. This studyusesthe population ofthe subject are 47 teachers andemployee. Datawere collectedthrough2scalesarePerception toward Psychosocial Work Environment Scale, andOrganizational CommitmentScale. Analysis method in this research used simple regression analysis. The data were analyzed by simple regression analysis. The result is Fscore> F table (35,184 > 4,050), with t score (5,932) > t table (2,021), and the totaleffect =43,9%. That result show that Hypothesis null (Ho) rejected, it is mean perception toward psychosocial work environment contribute significantly to the organizational commitment.The implication of this research is islamic psychosocial work environment is important to increasing the organizational commitment in islamic education institution.